Anti-nociceptive, anti-inflammatory and antipyretic activities of the ethanol root bark extract of Salacia lehmbachii in rats and mice - Akuodor, Godwin C.; Ohadoma, Sylvester C.; Ofor, Casimir C.; Megwas, Anthony U.; Chukwu, Leo C.; Ramalan, Mansur A.; Okoroafor, Dorcas O.; Chilaka, Kingsley C. (International Journal of Basic & Clinical Pharmacology, 2021)
Background: The decoction of the roots of Salacia lehmbachi is used in traditional medicine for the treatment of different diseases such as malaria pains diabetes and microbial infections. Methods: Phytochemical screening and oral acute toxicity tests were carried out on the ethanol root extract of the plant. Anti-nocicetive activity using acetic acid induced writhing and tail immersion method in mice, anti-inflammatory activity using carrageenan induced paw oedema in rats and xylene induced ear oedema test in mice and antipyretic activity using Brewer’s yeast and D-amphetamine induced pyrexia in rats were determined at 50 mg/kg, 100 mg/kg and 200 mg/kg doses of the root extract. Results: The ethanol root extract contain alkaloids, saponins, tannins, flavonoids, terpenoids, steroids and cardiac glycosides. The oral acute toxicity tests was found to be greater than 5000 mg/kg. The root extract and the standard drug (Aspirin) significantly (p<0.05 and p<0.01) decreased the number of writhes caused by acetic acid. The extract and morphine significantly (p<0.05 and p<0.01) prolonged reaction time in tail immersion model. The extract produced significant (p<0.05 and p<0.01) dose dependent inhibition of oedema which was comparable to aspirin in carrageenan induced paw oedema model. The root extract also demonstrated significant (p<0.05 and p<0.01) effect in xylene induced mouse ear oedema test compared to dexamethasone. The extract significantly decreased high temperature in both Brewer’s yeast and d-amphetamine induced pyrexia. Conclusions: Findings show that S. lehmbachii may provide a good source of plant compounds with analgesic, anti-inflammatory and antipyretic activities.